A comparative thermodynamic analysis of samarium and erbium oxide based solar thermochemical water splitting cycles. (14th September 2017) - Bhosale, Rahul R.; Kumar, Anand; AlMomani, Fares; Ghosh, Ujjal; Khraisheh, Majeda
Abstract: This paper reports a thermodynamic comparison between the samarium and erbium oxide based solar thermochemical water splitting cycles. These cycles are a two-step process in which the metal oxide is first thermally reduced into the pure metal, and the produced metal can be used to split water to produce H2 . The metal oxides can be reused for multiple cycles without consumption. The effect of water splitting temperature on various thermodynamic parameters which are essential to design the solar reactor system for the production of H2 via water splitting reaction using the samarium and erbium oxides is studied in detail. The total amount of solar energy needed for the thermal reduction of samarium and erbium oxides is estimated. The amount of heat energy released by the water splitting reactor is calculated. Also, the cycle and solar-to-fuel energy conversion efficiency for both cycles are determined by employing heat recuperation. Obtained results indicate that the efficiencies associated with these cycles are comparable to the previously studies thermochemical cycles. It is observed that higher water splitting temperature favors towards higher efficiencies. At constant thermal reduction temperature = 2280 K, by employing 50% heat recuperation, the solar-to-fuel energy conversion efficiency for the samarium cycle (30.98%) is observed to be higher than erbium cycle (28.19%). Highlights: For all T L, solar energy needed to run the erbium cycle is higher than samarium cycle. Re-radiation losses for both cycles decreases as the T L increases. Q ˙ s p l i t t i n g - E r is higher as compared to Q ˙ s p l i t t i n g - S m at all T L . η solar - to - fuel - Sm is higher (23.74%) than η solar - to - fuel - Er (21.32%) at T L  = 1200 K. Efficiency values for both cycles increases due to heat recuperation.